Observation of the decay B+ -> psi(2S)phi(1020)K+ in pp collisions at root s=8 TeV - (:unkn) unknown (ELSEVIER, 2017)
The decay B+ -> psi(2S) phi(1020) K+ is observed for the first time using data collected from pp collisions at root S = 8 TeV by the CMS experiment at the LHC, corresponding to an integrated luminosity of 19.6 fb(-1). The branching fraction of this decay is measured, using the mode B+ -> psi(2S) K+ as normalization, to be (4.0 +/- 0.4 (stat)+/- 0.6 (syst)+/- 0.2 (B)) x 10(-6), where the third uncertainty is from the measured branching fraction of the normalization channel. (C) 2016 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; B physics; Rare B decays